Three Decades of SSRI/SNRI Withdrawal Research: A Bibliometric and Science-Mapping Study - Akça, Erdoğdu (The European Research Journal, 2026)
Objectives: Selective serotonin reuptake inhibitors (SSRIs) and serotonin–norepinephrine reuptake inhibitors (SNRIs) are widely prescribed, and growing evidence highlights the clinical and methodological challenges of withdrawal during discontinuation. This study aimed to provide a comprehensive bibliometric map of SSRI/SNRI withdrawal research to clarify production patterns, citation structures, thematic evolution, and global collaboration. Methods: A comprehensive search of the Web of Science Core Collection (1995–2025) identified 652 original articles on SSRI/SNRI withdrawal, discontinuation, or tapering. Records were analyzed using the bibliometrix package in R for performance metrics, co-citation and keyword networks, and country–institution collaboration structures. Results: The corpus comprised 652 documents published in 308 journals, citing 18,957 references, with an annual growth rate of 7.79%. Articles received a mean of 41.6 citations. The Journal of Clinical Psychiatry (22 articles; h=20) and Journal of Clinical Psychopharmacology (18; h=14) were the most influential sources. Highly cited documents ranged from 270 to 730 citations, predominantly from Lancet, Pediatrics, The New England Journal of Medicine, and American Journal of Psychiatry. Keyword frequency was led by “depression” (n=172), “fluoxetine” (n=153), and “antidepressants” (n=152). The United States produced 240 articles (36.8%; 12,904 citations), forming the central hub of the collaboration network. Conclusions: SSRI/SNRI withdrawal research shows concentrated authorship, journal anchoring, and geographically centralized knowledge production, with emerging themes in tapering, pregnancy outcomes, and pharmacogenetics.